Pelatihan Penerapan Metode Full Costing Dalam Perhitungan Harga Pokok Penjualan Untuk Penetapan Harga Jual Produk - Martika, Lia Dwi; Puspasari, Oktaviani Rita; Syarifudin, Syahrul (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2022)
The calculation and drafting of cost of goods is an important matter. So that the business owner does not experience a loss, the selling price of an item cannot be determined arbitrarily. Many business owners do not know how to determine the selling price because they do not know the concept of calculating the cost of goods sold (COGS) for the resulting products. Cost of Goods Sold (COGS) is the amount of expenditure and expenses that are allowed, either directly or indirectly, to produce goods or services in the conditions and places where the consumer can sell or use the goods. So there are important benefits that business owners must realize that the Cost of Goods Sold (HPP) must be recorded and calculated properly, so that the selling price is correct. The method used was short training and mentoring which was carried out with individual and classical approaches. The results of this service are expected to provide knowledge and insight for business owners so that they can use financial information carefully for decision making and be able to apply bookkeeping in good business management.Keywords: Full Costing, Cost of Goods Sold, Selling Price